Structural and ultrastructural characterization of the floral lip in gongora bufonia (Orchidaceae): Understanding the slip-and-fall pollination mechanism - Adachi, Sérgio Akira [UNESP]; Machado, Silvia Rodrigues [UNESP]; Guimarães, Elza [UNESP] (Canadian Science Publishing, 2015)
In this study, we investigated the pollination ecology and floral lip morphology of Gongora bufonia Lindl., an epiphytic orchid from tropical forest, to better understand the peculiarities of its unusual pollination mechanism. Field observations on pollination were performed and floral lip samples were prepared for anatomical, histochemical, and ultrastructural analyses. Male Eufriesea violacea (Blanchard) bees use the second and third pairs of legs to hold on the epichile and collect the fragrance in the hypochile region. During this process, the bee slips and falls on the column and receives the pollinarium, which is attached to the rear edge of the bee’s scutellum. A subsequent visit (usually to another flower) and fall through the flower may result in insertion of a pollinium into the stigmatic slit at the apex of the column. The fragrance production occurs in the hypochile region, specifically in the papillose epidermal cells and in the subepidermal parenchyma layers. The wax production occurs in the epichile region, exclusively in the epidermal cells. The cells of both regions, hypochile and epichile, have ultrastructural features of lipophilic secretion. The slippery quality of the epichile epidermis is due to wax deposits; this is probably essential to the pollination mechanism of G. bufonia.
Keywords: Fragrance; Gongora; Orchidaceae; Pollination; Ultrastructure; Wax